Current Problems of Arts Education and Training in Primary Education - Zuzana Sláviková (Ignatianum University Press, 2019)
In this paper we would like to highlight the current developments in the veld of arts pedagogy in the context of wider trends in the philosophical and psychological thinking, which points to the the most signivcant aims of arts education, but which in teaching practice has still not been suuciently accepted. At the same time, the paper aims to draw attention to a very etective and unique concept as proposed by the Slovak composer and pedagogue Juraj Hatrík. This musical-pedagogical method very etectively solves the identived problems of musical pedagogy, starting at the elementary level, where he addressed mainly conceptual and methodical questions. Allmost all projects and methodologies of that are proven and etective in practice.